La valoración económica de las empresas manufactureras industriales en el Ecuador. aplicación del método multicriterio - Vilema Vargas, Anais Micaela (2024)
ABSTRACT: This degree work aims to establish the economic value based on the multicriteria method of industrial manufacturing companies in Ecuador in 2021. The method developed herein is called a hypothetical, deductive method because a hypothesis is proposed that will be subject to verification of industrial manufacturing companies in Ecuador, and based on this analysis, conclusions and recommendations were established. To carry out the investigation, the Diakauloki Multicriteria method was used because this model helps compare the values of the asset with those of others with the same characteristics and price. By applying the Multicriteria method, the real economic value of industrial manufacturing companies in Ecuador can be determined by comparing it with the financial value that is reflected through their financial statements, verifying the real value for its managers, as well as for partners and shareholders. Knowledge of the impact of their decisions, appropriately addressing corporate operations and public offerings, among others. Since knowledge of this is of great relevance to the current and future economic context. Keywords: Economic value; Multicriteria Method; CRITIC; Valuation ratio, financial statements.